Pengembangan Buku Ajar E-Book Interaktif Berbasis Heyzine Flipbook pada Mata Pelajaran Al-Qur’an Hadist Kelas VIII di MTsN 4 Nganjuk - Shofiyani, Amrini; Nazula, Fakhrun Nisa’ (ALSYS, 2025)
Learning Al-Qur’an Hadith in madrasahs still faces challenges related to low student interest and understanding, largely due to the use of conventional instructional media that are unengaging and misaligned with the characteristics of digital-era learners. This study aims to develop an interactive e-book based on Heyzine Flipbook for the eighth-grade Al-Qur’an Hadith subject at MTsN 4 Nganjuk. The method used is Research and Development (R&D) with the 4D model: Define, Design, Develop, and Disseminate. Instruments included validation questionnaires by content and media experts, as well as pretest and posttest assessments with 30 students to measure product effectiveness. Validation results indicated that the e-book is highly feasible for use, with feasibility scores of 86.65% from content experts and 85.8% from media experts. Effectiveness testing showed an average N-Gain score of 65.74%, categorized as moderate. The e-book includes interactive features such as digital navigation, practice questions, and supporting visual media that enhance students’ understanding of the material. The study concludes that the interactive e-book based on Heyzine Flipbook is feasible and effective as a learning medium. Its implications include providing teachers with an innovative instructional alternative and encouraging madrasahs to support the development of digital teaching media as part of 21st-century learning transformation.